2015
DOI: 10.18203/2320-6012.ijrms20150316
|View full text |Cite
|
Sign up to set email alerts
|

Study of insulin levels in hypothyroidism patients

Abstract: INTRODUCTIONHypothyroidism is a clinical syndrome due to deficiency of thyroid hormones which results in a generalized slowing down of metabolic 1 process. It is a common disorder that occurs in mild to severe forms in 2% to 15% of the population. Women are affected more often than men and both sexes are affected more frequently with increasing age. Clinical symptoms can range from the obvious and easy to recognise lethargy, fatigue and cold intolerance to more subtle, subclinical disease with general symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
3
0
5
Order By: Relevance
“…In the present study we have explored the possible linkage among TSH, insulin resistance and serum total cholesterol in newly diagnosed hypothyroidism patients [47,48]. In this study total cholesterol are 233.66 ± 63.46 highly significantly elevated, compared to 222 ± 53 mg/dl in on study done by Guddanti Rajeswari et al in hypothyroidism pateients [49].…”
Section: Methodsmentioning
confidence: 74%
“…In the present study we have explored the possible linkage among TSH, insulin resistance and serum total cholesterol in newly diagnosed hypothyroidism patients [47,48]. In this study total cholesterol are 233.66 ± 63.46 highly significantly elevated, compared to 222 ± 53 mg/dl in on study done by Guddanti Rajeswari et al in hypothyroidism pateients [49].…”
Section: Methodsmentioning
confidence: 74%
“…In a study done by Singh et al [8] in year 2010 found that TSH levels were positively correlated with serum insulin levels with significant P value<0.01. In one another study done by Rajeswari et al [9] in year 2015 found that TSH levels were positively correlated with insulin in patients with subclinical hypothyroidism (SCH). There study indicated that insulin resistance was present not only in overt hypothyroidism but it was significantly present in subclinical hypothyroidism also.…”
Section: Discussionmentioning
confidence: 99%
“…In one another study done by Rajeswari G. et al in year 2015 found that TSH levels were positively correlated with insulin in patients with subclinical hypothyroidism(SCH). [23] Their study indicated that insulin resistance was present not only in overt hypothyroidism but it was significantly present in subclinical hypothyroidism also. In our study in group 1 there were 14(28%) males, 36(72%) females, mean age of patients was 56.86±9.689 and 21(42%) were hypertensive.…”
Section: Discussionmentioning
confidence: 99%